Obremenjenost zraka s cvetnim prahom - Kofol-Seliger, Andreja (Naše okolje, 2023)
The pollen measurement was performed on four sites in Slovenia: in Lendava in the Pomurje region, Maribor in the Štajerska region, in the central part of the country in Ljubljana, and on the Adriatic coast in Izola. An outlook for the September is included in the article.
Keywords: alergeni; alergije; alergijske reakcije; cvetni prah